The Special Tribunal for Lebanon (STL): Selective Justice and Political Maneuvers - Nashabe, Omar (International Journal of Criminology and Sociology, 2012)
The Special Tribunal for Lebanon is the most recently established international criminal tribunal. It was created by the UN Security Council in 2007 to prosecute those responsible for the assassination of former Prime Minister Rafik Hariri and others in 2005. However, the process of creating the tribunal did not comply with Lebanese Constitutional provisions. This paper sheds light on the politics of selective justice, recalling impunity in Lebanon before and after Hariri’s assassination. It also exposes the UN Security Council’s double standards and argues that by creating the tribunal under Chapter VII of the UN Charter, Lebanon’s sovereignty was compromised. The international criminal investigation leading to the recent indictment seemed also highly controversial. The political motivations behind the Special Tribunal’s standards are exposed in this paper, whereas numerous breaches of local legal provisions, ethics and confidentiality are shown. The paper concludes with a discussion of suggested remedies.